The first case of micropapillary adenocarcinoma associated with cystic airspace in a non‐smoking man. Issue 2 (12th December 2019) - Takahashi, Saeko; Murata, Saori; Seki, Reishi; Kuriyama, Shoji; Kaji, Masahiro; Nakamura, Morio
Abstract : Lung cancers associated with cystic airspaces are attracting increasing attention because of delayed diagnosis. The cancers that usually occur in smokers comprise lepidic, papillary, and/or acinar adenocarcinoma, but a micropapillary type has not been described to date. Pulmonary micropapillary adenocarcinoma was added to the 2015 World Health Organization (WHO) classification system as a new subtype with a notably poor prognosis. We describe the first micropapillary adenocarcinoma of the lung associated with cystic airspaces in a 79‐year‐old non‐smoking man. Abstract : Lung cancers associated with cystic airspaces are typically adenocarcinoma with lepidic, papillary, and/or acinar patterns and are usually found in smokers. To date, there has been no report of those cancers revealing micropapillary patterns. Here, we describe the first case of pulmonary micropapillary adenocarcinoma associated with cystic airspaces in 79‐year‐old non‐smoking man.